The Extent of Nursery Nurses’ Possession of the Skill of Storytelling from their Perspectives (A field study in Tartous) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The current research aimed to show the extent of nursery nurses’ possession of storytelling skill from their perspectives. The research sample consisted of 198 nurses from both official and private nurseries in Tartous City in the academic year of 2015/2016. In this research the researcher adopted the descriptive approach to get the results, and she used, as a research tool, a questionnaire designed by her and edited by a group of specialists. The results showed that the nursery nurses had the skill of storytelling at a fair degree in the terms of both the preparation of the story and its discussion after telling it at a high degree in the terms of storytelling. In addition, there are statistically significant differences in the perspectives of the nursery nurses about how much they have the skill of storytelling according to both variables of the nursery’s affiliation and experience on the behalf of the official nurseries and nurses with experience of six years or more. The results also showed that there are no statistically significant differences in the perspectives of nurses according to the variable of scientific and educational qualification.